Enhanced performance and stability of low-bandgap mixed lead–tin halide perovskite photovoltaic solar cells and photodetectors via defect passivation with UiO-66-NH2 metal–organic frameworks and interfacial engineering. Issue 9 (30th May 2022) - Chang, Chih-Yu; Wu, Kuan-Hsi; Chang, Chun-Ya; Guo, Rui-Fang; Li, Guan-Lin; Wang, Cheng-Yu
Abstract : The incorporation of the UiO-66-NH2 metal–organic frameworks as the processing additive into mixed lead–tin halide perovskites can effectively passivate the defects, enabling the photovoltaic devices to exhibit high performance and good stability. Abstract : Despite the remarkable progress in perovskite optoelectronic devices, the realization of high-performance and stable devices based on low-bandgap mixed lead (Pb)–tin (Sn) halide remains highly challenging. Here we present a promising strategy to improve the performance and stability of mixed lead–tin halide perovskite photovoltaics by using metal–organic frameworks (MOFs) as additives, including UiO-66 and UiO-66-NH2 . Compared with UiO-66, the electron-donating amine group of UiO-66-NH2 can interact with under-coordinated metal cations in the perovskite crystals ( i.e., Pb 2+ or Sn 2+ ), leading to efficient trap-state passivation and thus superior device performance. With interfacial engineering via molecular doping, the resultant devices exhibit a high-power conversion efficiency of 13.93% and substantially improved ambient stability. To the best of our knowledge, the device performance demonstrated herein represents the highest value ever reported for CH3 NH3 Sn x Pb1− x I3 -based perovskite solar cells with an active area larger than 0.1 cm 2 . Importantly, this strategy is also applicable to perovskite photodetectors (PDs), delivering record-high performance for low-bandgap (≤1.3 eV) perovskite PDs. This work provides a new route to simultaneously improve the performance and stability of mixed Pb–Sn perovskite photovoltaics based on a facile strategy, which can accelerate perovskite-based optoelectronics toward future commercialization.